STUDI PENGELOLAAN SAMPAH DILIHAT DARIASPEK TEKNIS KESEHATANDI KABUPATEN KARIMUN - Sugema, Brata; Hamidy, Rasoel (Jurnal Kajian Lingkungan, 2013)
Waste is all product or object of rest in the form of solid as effect of human being activity,assumed no advantage and do not desire by its owner and thrown as goods which of no use.Make-up of the amount of resident of human being activity amount and resident directly canimprove the amount of yielded waste production in Karimun District. Considering hygienerepresent requirement and rights with hence needed by strategy in managing waste start fromplace of management and transportation finally matching with technical aspect of healthspecified by government. This research is descriptive which depict system management ofhealth aspect condition and waste residing in around place management of waste in KarimunDistrict. Way of collecting data with direct interview and admission filling of quisioner is andalso conducted observation in management of waste in Karimun District. Management ofwaste in Karimun District evaluated from technical aspect of health still not yet followedhealth aspect in the case of ready facility and medium also system management ofwaste.Thereby need serious attention to anticipate early possible the existence of generateddisease and contamination of waste exist in karimun District and its need cooperationbetween government with society in improving healthy environment to society.